Immanuel Kant's Critique of the Ontological Argument: Challenging the Existence of God - Dina; Mohammad Muafi Himam (AN NUR: Jurnal Studi Islam, 2023)
This study described Immanuel Kant’s critique of the ontological argument, which he considered weak and flawed in proving the existence of God. Kant had been criticized by many philosophers -the philosophers who defended the ontological argument- as soon as he put forward the critique of the ontological argument. Immanuel Kant argued against the analyticity of "exists" and its status as a real predicate. He criticized ontological arguments, highlighting the distinction between logical and ontological necessity. Kant rejected attempts to derive the existence of a supreme being from concepts, stating that existence transcended conceptual boundaries. While sensory objects could be known through our senses, the existence of pure reason or thought remained unknowable without a priori knowledge. Our awareness of existence pertained to the unity of experience, and any existence beyond it was an unjustifiable illusion. In this study, someone would not disclose the critique of Kant’s critique of ontological argument.